2018
DOI: 10.1002/admi.201800530
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructural Analysis of Porous Oblique Angle Deposited (OAD) Multilayer Systems by Grazing‐Incidence Small‐Angle X‐Ray Scattering

Abstract: Additional Information:Question ResponsePlease submit a plain text version of your cover letter here.If you are submitting a revision of your manuscript, please do not overwrite your original cover letter. There is an opportunity for you to provide your responses to the reviewers later; please do not add them here. Dear Editor,Enclosed we are sending to you a conscientiously revised manuscript of the previous "Nanostructural Analysis of Porous Oblique Angle Deposited (OAD) Multilayer Systems by Grazing-Inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…It means the formation of a higher electron density distribution of nanocolumnar structure takes place along Co flux arrival direction. Moreover, it is as per the earlier studies for OAD on planner template, where significant shadowing effect is found to be responsible for this asymmetry in the electron density along the azimuthal direction [51]. 43 • , whereas the average separation between nanocolumns is found out to be 12.7 nm.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…It means the formation of a higher electron density distribution of nanocolumnar structure takes place along Co flux arrival direction. Moreover, it is as per the earlier studies for OAD on planner template, where significant shadowing effect is found to be responsible for this asymmetry in the electron density along the azimuthal direction [51]. 43 • , whereas the average separation between nanocolumns is found out to be 12.7 nm.…”
Section: Resultssupporting
confidence: 85%
“…The lateral spacing of the nanostructure, as calculated, is found to be 14.8 nm. Observation of the broad peak only along -q y side confirms the formation of inclined columnar nanostructures [49][50][51][52][53]. The angle (β) of tilted columnar morphology with respect to substrate normal is obtained based on the slope of intensity elongation I (Fig.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation